Marketing management: Indian cases (Pearson India, 2017)
Marketing Management: Indian Cases is a casebook companion aimed to help readers understand the concepts of marketing in the Indian context. The booklet carries 23 contemporary cases which provide in-depth analysis of different marketing principles and theories as applied by various companies in India and Asia. This casebook will be useful for students pursuing MBA and PGDBM courses.